Tryptanthrin exerts anti-breast cancer effects both in vitro and in vivo through modulating the inflammatory tumor microenvironment - Zeng Qingfang; Luo Cairong; Cho Junlae; Lai Donna; Shen Xiangchun; Zhang Xiaoyan; Zhou Wei (Acta Pharmaceutica)
Tryptanthrin is an indole quinazoline alkaloid from the indigo-bearing plants, such as Isatis indigotica Fort. Typically, this natural compound shows a variety of pharmacological activities such as antitumor, antibacterial, anti-inflammatory and antioxidant effects. This study was conducted to assess the antitumor activity of tryptanthrin in breast cancer models both in vitro and in vivo, and to explore the important role of the inflammatory tumor microenvironment (TME) in the antitumor effects of tryptanthrin. Human breast adenocarcinoma MCF-7 cells were used to assess the antitumor effect of tryptanthrin in vitro. MTT assay and colony formation assay were carried out to monitor the antiproliferative effect of tryptanthrin (1.56~50.0 μmol L−1) on inhibiting the proliferation and colony formation of MCF-7 cells, respectively. The migration and invasion of MCF-7 cells were evaluated by wound healing assay and Transwell chamber assay, respectively. Moreover, the 4T1 murine breast cancer model was established to examine the pharmacological activity of tryptanthrin, and three groups with different doses of tryptanthrin (25, 50 and 100 mg kg−1) were set in study. Additionally, tumor volumes and organ coefficients were measured and calculated. After two weeks of tryptanthrin treatment, samples from serum, tumor tissue and different organs from tumor-bearing mice were collected, and the enzyme-linked immunosorbent assay (ELISA) was performed to assess the regulation of inflammatory molecules in mouse serum. Additionally, pathological examinations of tumor tissues and organs from mice were evaluated through hematoxylin and eosin (H&E) staining. The expression of inflammatory proteins in tumor tissues was measured by immunohistochemistry (IHC) and Western blotting. Tryptanthrin inhibited the proliferation, migration and invasion of MCF-7 cells, up-regulated the protein level of E-cadherin, and down-regulated those of MMP-2 and Snail, as suggested by the MCF-7 cell experiment. According to the results from in vivo experiment, tryptanthrin was effective in inhibiting tumor growth, and it showed favorable safety without inducing the fluctuations of body mass and organ coefficient (p > 0.05). In addition, tryptanthrin also suppressed the expression levels of NOS1, COX-2 and NF-κB in mouse tumor tissues, and regulated those of IL-2, IL-10 and TNF-α in the serum of tumor cells-transplanted mice. Tryptanthrin exerted its anti-breast cancer activities through modulating the inflammatory TME both in vitro and in vivo.